SOLEMNITY TO TRIVIALITY: DEATH, CAPITALISM AND THE WRITERS’ IMAGINATION - UNUAJOHWOFIA, Henry Obakore; EDEGBE, Kennedy Omoruyi (EBSU Journal of Social Sciences and Humanities, 2024)
One issue that has preoccupied writers of the novel in Africa is the interplay between capitalism and death. Death is an avenue for transiting the physical world to that of the ancestors in the African cosmogonic epistemology. Capitalism has added new vistas in the way African novelists explore the multi-dimensions in the motif of death in African narratives. This paper argues that African narrators have decolonized death from being only a solemn transition to the ethereal world of ancestors to reconceptualising death as a means of attaining wealth. Adopting the postcolonial literary theory, the paper uses illustrations from Chinua Achebe’s Things Fall Apart (1958), Zakes Mda’s Ways of Dying (1995), Naguib Mahfouz’s Midaq Alley (1996), Chris Abani’s Graceland (2004), and Toni Kan’s The Carnivorous City (2016) to point out that the themes of transition, respect, greed, materialism and murder are enabling novelists to portray death as a path to material gains. While the techniques of flashback, contrast, symbolism and allusion create the necessary comic and aesthetic ambience to the shifting narrative of death, the paper concludes that as death becomes a means of survival in the physical world, the practicality of the concept of life after death is becoming difficult to comprehend.